Estrés académico y logros de aprendizaje en el área de desarrollo personal, ciudadanía y cívica en estudiantes de secundaria de la institución educativa colegio Experimental UNAP, distrito de San Juan 2024 - Coelho Moreno, Karen Elsa (2025)
The study set out the task of linking the level of academic stress and learning achievements among secondary school students of an educational institution. It assumed the quantitative route of a cross-sectional correlational type with a specific cross-sectional correlational design. The population was made up of 464 students from which a sample of 107 high school students was extracted from non-probabilistic sampling of the judgment type. The survey was used as a technique with two evaluation instruments, one for each variable. After systematizing the information and applying Spearman's Rho test, it shows a very strong positive correlation. This conclusion is based on a p-value of (0.000), a value lower than (0.05), which confirms the existence of a very strong positive correlation between academic stress and significant learning achievements. This positive and very strong correlation is supported by the statistical value of Spearman's Rho=0.885. Finally, at a confidence level of 95%, as a corollary, the existence of a relationship between academic stress and learning achievements in high school students of the IE Colegio Experimental UNAP, San Juan Bautista 2024 district is affirmed.